Ability of Older Adults to Report Elder Abuse: An Emergency Department–Based Cross‐Sectional Study. Issue 1 (9th January 2020) - Richmond, Natalie L.; Zimmerman, Sheryl; Reeve, Bryce B.; Dayaa, Joseph A.; Davis, Mackenzie E.; Bowen, Samantha B.; Iasiello, John A.; Stemerman, Rachel; Shams, Rayad B.; Haukoos, Jason S.; Sloane, Philip D.; Travers, Debbie; et al.
Abstract : OBJECTIVES: To characterize assessments of a patient's ability to report elder abuse within the context of an emergency department (ED)–based screen for elder abuse. DESIGN: Cross‐sectional study in which participants were screened for elder abuse and neglect. SETTING: Academic ED in the United States. PARTICIPANTS: Patients, aged 65 years and older, presenting to an ED for acute care were assessed by trained research assistants or nurses. MEASUREMENTS: All patients completed the four‐item Abbreviated Mental Test 4 (AMT4), then completed a safety interview (using the Emergency Department Senior Abuse Identification tool) designed to detect multiple domains of elder abuse and received a physical examination. Based on the cognitive assessment and safety interview, assessors ranked their confidence in the patient's ability to report abuse as absolutely confident, confident, somewhat confident, or not confident. To assess interrater reliability, two assessors independently rated confidence for a subset of patients. RESULTS: Assessors suspected elder abuse in 18 of 276 patients (6.5%). Assessors were absolutely confident in the patient's ability to report abuse for 95.7% of patients, confident for 2.5%, somewhat confident for 1.5%, and not confident for 0.3%. Among patients with an AMT4 of 4 (n = 249), assessors were confident or absolutely confident in 100% of patients. Among patients with an AMT4 of less than 4 (n = 27), they were confident or absolutely confident in the patient's ability to report abuse for 81% of patients, including 11 of 12 patients with mild cognitive impairment and 7 of 11 patients with severe cognitive impairment. For patients receiving paired evaluations (n = 131), agreement between assessors regarding patient ability to report abuse was 97% (κ = 0.5). CONCLUSIONS: In this sample of older adults receiving care in an ED, research assistants and nurses felt that the vast majority were able to report elder abuse, including many patients with cognitive impairment. J Am Geriatr Soc 68:170–175, 2019